Combination of Aspergillus niger MJ1 with Pseudomonas stutzeri DSM4166 or mutant Pseudomonas fluorescens CHA0-nif improved crop quality, soil properties, and microbial communities in barrier soil - Ni, Haiping; Wu, Yuxia; Zong, Rui; Ren, Shiai; Pan, Deng; Yu, Lei; Li, Jianwei; Qu, Zhuling; Wang, Qiyao; Zhao, Gengxing; Zhao, Jianzhong; Liu, Lumin; et al. (Frontiers in Microbiology, 2023)
This study investigated the effect of phosphate-solubilizing bacteria, Aspergillus niger MJ1 combined with nitrogen-fixing bacteria Pseudomonas stutzeri DSM4166 or mutant Pseudomonas fluorescens CHA0-nif on crop quality, soil physicochemical properties, and microbial communities in the acid and salinized soil. A total of 5 treatments were set: regular fertilization (T1), regular fertilization with MJ1 and DSM4166 (T2), regular fertilization with MJ1 and CHA0-nif (T3), 30%-reducing fertilization with MJ1 and DSM4166 (T4), and 30%-reducing fertilization with MJ1 and CHA0-nif (T5). It was found that the soil properties (OM, HN, TN, AP, AK, and SS) and crop quality of cucumber (yield production, protein, and vitamin C) and lettuce (yield production, vitamin C, nitrate, soluble protein, and crude fiber) showed a significant response to the inoculated strains. The combination of MJ1 with DSM4166 or CHA0-nif influenced the diversity and richness of bacterial community in the lettuce-grown soil and showed no significant effects on the cucumber-grown soil microbial community and the fungal community of lettuce-grown soil. The organismal system-, cellular process-, and metabolism-correlated bacteria and saprophytic fungi were enriched, which were speculated to mediate the response to inoculated strains. pH, OM, HN, and TN were identified to be the major factors correlated with the soil microbial community. The inoculation of MJ1 with DSM4166 and CHA0-nif could meet the requirement of cucumber and lettuce growth after reducing fertilization, which provides a novel candidate for the eco-friendly technique to meet the carbon-neutral topic.